The impact of a stewardship program on antibiotic administration in community-acquired pneumonia: Results from an observational before-after study. (February 2021) - Fally, Markus; Diernaes, Emma; Israelsen, Simone; Tarp, Britta; Benfield, Thomas; Kolte, Lilian; Ravn, Pernille
Highlights: An antibiotic stewardship program led to a significant reduction of antibiotic exposure in CAP. Furthermore, more patients were treated with a guideline-conform empiric antibiotic. The main results were strengthened by multiple sensitivity analyses. The positive effect of antibiotic stewardships in CAP cannot be denied. Abstract: Background: A majority of patients with community-acquired pneumonia (CAP) receive antibiotics. According to the evidence, 5–7 days of treatment should be sufficient for most patients. Many, however, are treated longer than recommended. We have previously conducted a quality improvement study to ensure guideline-conform treatment for CAP. However, the impact of the interventions on antibiotic use has not been investigated. Objective: To estimate the impact of an eight-month stewardship program on antibiotic use. Methods: We conducted a before-after study comparing a four-month baseline period with data from a corresponding follow-up period. We performed univariable and multivariable logistic regression to compare odds for ≤7 days of total antibiotic treatment, ≤3 days of intravenous treatment and the proportion of correct empiric antibiotics. As sensitivity analysis, we repeated the univariable logistic regression on a propensity score-matched cohort by using the same variables we used for adjustments in the multivariable analysis. We also performed subgroup analyses for patients stable ≤72 h of admission. Results: In total, 771 patients were included. Compared to preintervention, the unadjusted odds ratio (OR) for ≤7 days of total antibiotic treatment were 1.84 (95% CI 1.34–2.54) for the whole population and 2.08 (1.41–3.10) for the stable patients. The OR for ≤3 days of intravenous antibiotics were 1.16 (0.87–1.54) and 1.38 (0.87–2.22), respectively. The OR for correct empiric antibiotics were 1.96 (1.45–2.68) and 1.82 (1.23–2.69). Comparable results regarding all outcomes were derived from the other analyses. Conclusion: The program resulted in a significantly lower overall antibiotic exposure and a higher proportion of patients treated with the recommended antibiotics without a the reduction of exposure to intravenous antibiotics significantly.